The social history of the Third Reich : 1933 - 1945 - Ayçoberry, Pierre (New Press [u.a.], 2000)
Machine generated contents note: PART i: THE INVASION OF POLITICS: 1933-1939 15 -- 1. Violence 17 -- Brute Violence: The SA 17 -- Systematic Terror: The SS 26 -- The Victims: The Discontented and Those Who Resisted 37 -- The Victims: "Those Alien to the Community" 49 -- The Concentration Camps 59 -- 2. The Myth of the People's Community 65 -- A Community of the People, or of the Race? 65 -- The Strategy of Communication 67 -- The Party: Was It a Prefiguration or a -- Caricature of the Community? 79 -- How the Myth was Received by Public Opinion 89 -- 3. The Illusions, Collusions, and Disillusions of the Elites 0oo -- Doubts of the Leading Social Groups 100 -- Getting Everyone to "Fall into Line," 1933-1934 io6 -- "Continue to Function" At Least, 1934-1938 124 -- 4. The Conquest of the Masses 44 -- Were the Middle Classes Rewarded? 145 -- A Disintegrating Working Class 156 -- The Conquest of Women and Young People 172 -- 5. Radicalization, 1938-1939 19o -- The Battle Against the Churches 19o -- Marching as to War 196 -- PART 2: WARTIME SOCIETY: 1939-1945 207 -- 6. The Dissolution of Civil Society 209 -- Families Split Apart 209 -- Towns Reduced to Rubble: Resourcefulness -- and New Solidarities 218 -- The Mixing and Migrations of Rural Populations 226 -- Militarized Workers 231 -- 7. The Nazi Party and the Social Authorities 245 -- The High-Ranking Officials: Caught Between -- Impotence and Conspiracy 246 -- The Ambitions and the Discredit of the Party 251 -- The Major Business Bosses Move Toward Limitless Expansion 257 -- 8. Toward Utopia through Terror 269 -- The SS Empire 269 -- How to Live with Ten Million Excluded People 280 -- The Final Solution to "TheJewish Question" 289 -- 9. The Front and the Rear 305 -- The Avenging Army, 1939-1940 306 -- The Crusading Army, 1941-1943 309 -- The Wehrmacht and War Crimes 318 -- The Military Plots and the Defeat 327 -- Morale at the Rear 333 -- Conclusion 344 -- Chronology 351 -- Bibliography 356 -- Abbreviations 378